2019
DOI: 10.3390/agriculture9080170
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Sugarcane Production by Small-Scale Growers in Ndwedwe Local Unicipality, South Africa

Abstract: Sugarcane is an important crop worldwide due to its many nutritional and economic uses. Small-scale sugarcane growers (SSGs) are a significant sector of sugarcane production in South Africa. However, the number of SSGs is noted to have declined from as early as the 2000s to the present time. As a result of the declining sugarcane production, there are now generally fewer SSGs. However, it is not clear cut as to what caused the decrease in sugarcane production by SSGs. The primary objective of this paper is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
(16 reference statements)
0
2
0
1
Order By: Relevance
“…The sugar industry recommends 24 hours interval from burning to cutting (harvesting) to prevent sucrose depletion. Each one-day delay results in a sucrose loss of 2.2% per day (Zulu et al, [25] .…”
Section: Time Delay In Cutting Transportation and Processing Of Burnt...mentioning
confidence: 99%
“…The sugar industry recommends 24 hours interval from burning to cutting (harvesting) to prevent sucrose depletion. Each one-day delay results in a sucrose loss of 2.2% per day (Zulu et al, [25] .…”
Section: Time Delay In Cutting Transportation and Processing Of Burnt...mentioning
confidence: 99%
“…Nilai koeifisen variabel pupuk K sebesar -0,775 menunjukkan hubungan yang negatif, setiap penambahan penggunaan pupuk K sebesar 1%, maka akan mengurangi pendapatan usahatani tebu sebesar 0,775%. Hal ini sesuai dengan temuan penelitian sebelumnya bahwa penggunaan pupuk berpengaruh signifikan terhadap produksi usahatani tebu (Zulu et al, 2019).…”
Section: Faktor-faktor Yang Mempengaruhi Pendapatan Usahatani Tebuunclassified
“…The findings of this study showed that the rates of using fertilizer and pesticide, effective precipitation, and planted area of corn had a positive relationship in increasing corn yield. Zulu et al (2019) analyzed sugarcane production by small-scale growers in Ndwedwe Local Municipality, South Africa, using ordinary least squares (OLS) based on the Cobb-Douglas function. This study found that the quantity of labor and amount of chemicals applied had statistical significance and positively correlated with sugarcane production.…”
Section: Literature Reviewmentioning
confidence: 99%